Раскройте скобки и упростите выражение: а) m - (n+m);
б) (х + 32) - (х + 64);
в) x+(-x+y);
г) -(m — 47 + n) - (103 - т);
д) -(а - b) — b;
е) -(27 - а) + (-a +18);
ж)-(-62 +a+b) = (a - b+109);
3) -с+ (с - d).​

myagkixmatveeva myagkixmatveeva    3   29.07.2020 18:03    2

Ответы
netesa0202 netesa0202  15.10.2020 15:35
А) m - n - m = -n
б) х + 32 - х - 64 = -32
в) х - х + у = у
г) -m + 47 - n - 103 + t = -m-56-n+t
д) -а + b - b = -a
e) -27 + a - a + 18 = -9
ж) 62 - а - b
з) -с + с - d = -d
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика